THE EFFECT OF FINASTERIDE ON BLEEDING DURING TRANSURETHRAL RESECTION OF THE PROSTATE (Iraqi Journal of Medical Sciences, 2016)
Background: Finasteride is a selective 5-? reductase enzyme inhibitor that blocks the conversion of testosterone to dihydrotestosterone, down regulates prostatic angiogenesis and blood flow and promotes apoptosis of prostatic cells. It significantly decreases suburethral prostatic microvessel density in patients with benign prostatic hyperplasia, which may explain its efficacy for decreasing benign prostatic hyperplasia -associated bleeding. Transurtheral resection of the prostate is considered the gold standard operation for symptomatic benign prostatic hyperplasia. It is characterized by immediate treatment success with long-lasting improvement of symptoms.Objective:To study the effect of finasteride on bleeding during transurethral resection of the prostate.Methods: Thirty eight patients with benign prostatic hyperplasia underwent transurethral resection of the prostate. Patients were randomly assigned into two groups, the finasteride group (18 patients) and the control group (20 patients). The intra-operative bleeding was measured.Results:Statistically less significant bleeding during transurethral resection of the prostate in patients who were placed on 10 mg finasteride for 6 weeks prior to the surgery. Conclusion: Finasteride given daily for 6 weeks prior to transurethral resection of the prostate reduces time of surgery, bleeding, and irrigation fluid requirements.Keywords: Hematuria, Finasteride, Benign prostatic hyperalgesia.
Keywords: Hematuria; Finasteride; Benign prostatic hyperalgesia